The Influence of Conformity and Hedonistic Lifestyle With Consumptive Behavior - Gita Safitri; Netty Dyan Prastika; Nanik Handayani (Eduvest - Journal of Universal Studies, 2024)
This research aims to examine the impact of conformity and a hedonistic lifestyle on consumptive behavior among students of the Faculty of Social and Political Sciences at University X in Samarinda. A quantitative approach is applied, with a sample of 100 students selected through a simple random sampling technique. Data is gathered using scales measuring consumptive behavior, conformity, and hedonistic lifestyle, then analyzed using SPSS 25.0 for Windows. Findings indicate a significant influence of conformity and a hedonistic lifestyle on consumptive behavior (F = 52.100; p = 0.000; R² = 45%). Additionally, there is a strong correlation between conformity and consumptive behavior (β = 0.523; t = 7.060; p = 0.000).